The technological relationships between indigenous firms and foreign-owned MNCs in the European regions - John Cantwell; Simona Iammarino (European Regional Science Association (ERSA), 2001)
It has been argued that the accumulation of technological competence is a path-dependent and context-specific process, being partly firm-specific and partly location-specific. MNCs spread the competence base of the firm, and acquire new technological assets or sources of competitive advantage. For their part indigenous firms benefit from local knowledge spillovers from MNCs, given the access of the latter to complementary streams of knowledge being developed in other locations. This paper examines how the particular corporate technological trajectories of multinational corporations (MNCs) have interacted with spatially-specific resources for the creation of new competence in some of the leading regions in Europe. Yet foreign investments, and the associated skills and capabilities that they bring, are arguably of crucial importance as a catalyst for local growth: learning curve advantages are mainly people- and institution-embodied and regional systems may substantially benefit from global corporations investing in innovation and local human capital. Although a break has thus occurred with the conventional economic approach - in which spatial factors shaping innovation were usually considered secondary (if not thoroughly negligible) - too little is still known about the regional scope with respect to the geographical location of innovatory capacity in the global economy. This is all the more relevant in the presence of an in-depth process of economic integration, as is the case of the EU, which arose from the need to define the problems, and the policies aimed at solving them, in terms of geographical location and centre/periphery economic convergence. We use data on the patents granted in the United States to large firms for inventions emanating from research facilities located in eight selected European countries (Belgium, France, Germany, Italy, the Netherlands, Sweden, Switzerland and the UK) over a 27 year period (1969-1995). The location-specific patent data is complemented through the use of other indicators such as the regional distribution of expenditure on basic scientific research, and the R&D expenditure personnel given by the EU database New-Cronos-Regio. The aim is to improve our understanding of some aspects of the effects of Innovation and Globalisation on Firms and Regions - i.e. technological spillovers - by examining the patterns of technological (by technological field of the largest firms) and production (by industry of the output of the largest firms) specialisation in each region. Differences between the two specialisation profiles may be indicative of technological diversification by industry, and hence potential technological overlaps between industries. These overlaps may be more pronounced in higher order centres, due to their greater technological breadth (which may show a greater technological diversification within the typical industry represented in the region, and not merely a greater span of industries). We then distinguish between intermediate centres (with significant levels of technologically focused activity) and lower order regions (backward regions, with little activity at all). The patterns of technological diversification of industries are then checked by examining which firms are responsible for a positive technological specialisation in the case of a region that lacks specialisation in the equivalent industrial category, and how this fits into the overall pattern of technological diversification of the firms in question.
Keywords: 330